Why Choice Matters: Revisiting and Comparing Measures of Democracy - Heiko Giebler; Saskia P. Ruth; Dag Tanneberg (Politics and Governance, 2018)
Measures of democracy are in high demand. Scientific and public audiences use them to describe political realities and to substantiate causal claims about those realities. This introduction to the thematic issue reviews the history of democracy measurement since the 1950s. It identifies four development phases of the field, which are characterized by three recurrent topics of debate: (1) what is democracy, (2) what is a good measure of democracy, and (3) do our measurements of democracy register real-world developments? As the answers to those questions have been changing over time, the field of democracy measurement has adapted and reached higher levels of theoretical and methodological sophistication. In effect, the challenges facing contemporary social scientists are not only limited to the challenge of constructing a sound index of democracy. Today, they also need a profound understanding of the differences between various measures of democracy and their implications for empirical applications. The introduction outlines how the contributions to this thematic issue help scholars cope with the recurrent issues of conceptualization, measurement, and application, and concludes by identifying avenues for future research.
Additional information: Editorial of the issue “Why Choice Matters: Revisiting and Comparing Measures of Democracy”, edited by Heiko Giebler (WZB Berlin Social Science Center, Germany), Saskia P. Ruth (German Institute of Global and Area Studies, Germany), and Dag Tanneberg (University of Potsdam, Germany).
Keywords: 330; application; conceptualization; democracy; democratic quality; measurement